Cement stabilisation of subgrade soil for sustainable pavement structure - Ahmad Kamil, Arshad; Ekarizan, Shaffie; Khairil Azman, Masri; Putra Jaya, Ramadhansyah; Yulinar, Ismail (Springer, 2021)
Unsuitable or poor quality subgrade material requires proper treatment in order to make the subgrade suitable for overlying top layers of pavement for road construction. Stabilisation of the subgrade layer using cement is a method to improve the strength and stiffness of the subgrade, minimising the risk of road damage such as permanent deformation and improve the long-term performance of the pavement. This paper details a study on the soil–cement stabilisation method for a low-volume road in Malaysia. The scope of this study involved mix design in the laboratory and site verification. The laboratory tests involved soil classification, compaction test, unconfined compressive strength and California Bearing Ratio (CBR) tests while site verification tests comprised of field density test and unconfined compressive strength tests. From the laboratory tests, it was determined that the type of soil for the study area (silty clay) was suitable to be stabilised using cement based on the results obtained from soil classification test and unconfined compressive strength achieved of more than 0.8 MPa obtained after the addition of 5% cement by weight. Field density test achieved more than 95% laboratory com paction density and unconfined compressive strength of 1.01 MPa, indicating that the method was successfully implemented as site. It is recommended that future research should be carried out on more sites and on different types of soil to determine the suitability of cement as additive for subgrade stabilization in Malaysia.